Mechanism-based strategies to prevent salt sensitivity and salt-induced hypertension - Kurtz, Theodore W; Pravenec, Michal; DiCarlo, Stephen E (Clinical science (1979), 2022)
High-salt diets are a major cause of hypertension and cardiovascular (CV) disease. Many governments are interested in using food salt reduction programs to reduce the risk for salt-induced increases in blood pressure and CV events. It is assumed that reducing the salt concentration of processed foods will substantially reduce mean salt intake in the general population. However, contrary to expectations, reducing the sodium density of nearly all foods consumed in England by 21% had little or no effect on salt intake in the general population. This may be due to the fact that in England, as in other countries including the U.S.A., mean salt intake is already close to the lower normal physiologic limit for mean salt intake of free-living populations. Thus, mechanism-based strategies for preventing salt-induced increases in blood pressure that do not solely depend on reducing salt intake merit attention. It is now recognized that the initiation of salt-induced increases in blood pressure often involves a combination of normal increases in sodium balance, blood volume and cardiac output together with abnormal vascular resistance responses to increased salt intake. Therefore, preventing either the normal increases in sodium balance and cardiac output, or the abnormal vascular resistance responses to salt, can prevent salt-induced increases in blood pressure. Suboptimal nutrient intake is a common cause of the hemodynamic disturbances mediating salt-induced hypertension. Accordingly, efforts to identify and correct the nutrient deficiencies that promote salt sensitivity hold promise for decreasing population risk of salt-induced hypertension without requiring reductions in salt intake.
Keywords: kardiovaskulární nemoci; Cardiovascular Diseases; kuchyňská sůl; hypertenze; krevní tlak; lidé; Humans; Hypertension; sodík; Blood Pressure; Sodium Chloride, Dietary; Sodium